The theatre student: Gilbert and Sullivan production - Kline, Peter (New York, 1972)
Describes the plot and characters of the Gilbert and Sullivan operet tas and discusses staging, casting, and other aspects of production for an amateur company.
Bibliography: p. 295-299.
Keywords: Gilbert, W. S. -- 1836-1911.; Sullivan, Arthur, -- 1842-1900.; Gilbert, W. S. -- 1836-1911.; Sullivan, Arthur, -- 1842-1900.; Operetta; Amateur theater; Operetta; Amateur theater